A Novel Role for the Zinc-Finger Transcription Factor EGL-46 in the Differentiation of Gas-Sensing Neurons in Caenorhabditis elegans. Issue 1 (12th November 2014) - Romanos, Teresa Rojo; Petersen, Jakob Gramstrup; Riveiro, Alba Redo; Pocock, Roger
Abstract: Oxygen (O2 ) and carbon dioxide (CO2 ) provoke distinct olfactory behaviors via specialized sensory neurons across metazoa. In the nematode C. elegans, the BAG sensory neurons are specialized to sense changes in both O2 and CO2 levels in the environment. The precise functionality of these neurons is specified by the coexpression of a membrane-bound receptor-type guanylyl cyclase GCY-9 that is required for responses to CO2 upshifts and the soluble guanylyl cyclases GCY-31 and GCY-33 that mediate responses to downshifts in O2 . Expression of these gas-sensing molecules in the BAG neurons is partially, although not completely, controlled by ETS-5, an ETS-domain-containing transcription factor, and EGL-13, a Sox transcription factor. We report here the identification of EGL-46, a zinc-finger transcription factor, which regulates BAG gas-sensing fate in partially parallel pathways to ETS-5 and EGL-13 . Thereby, three conserved transcription factors collaborate to ensure neuron type-specific identity features of the BAG gas-sensing neurons.